Upaya Meningkatkan Kemampuan Guru dalam Penggunaan Metode Pembelajaran Melalui Supervisi Klinis di SD Sindet UPT PP Kecamatan Jetis Kabupaten Bantul - Heny Rismiati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
The purposes of this school action research are: 1)To improvethe ability of teachers in the use of learning methods through clinical supervision. 2) To find out the steps of improvementof the ability of teachers in the use of learning methods through clinical supervision at SD SindetJetis Sub-District Semester 2 in 2017/2018 school year. A teacher is required to have several abilities and skills as part of the teacher's professional competence.The school action research method consists of two cycles. Each cycle carried out in two meetings. Where in the procedure each cycle consists of planning, action, observation, and reflection. Data collection techniques in this study using observation, discussion, and interview. The research subjects consists of 7 (seven) teachers. The results of the study showed that there was an increase in the ability of teachers in the of learning method through clinical supervision in the second semester of the school year 2017/2018 at SD Sindet UPT PPK Jetis. In the first cycle, the results of the teacher's ability to prepare Lesson Plans (RPP) reached an average of 65%, the assessment of Teaching and Learning Activities (KBM) reached 62%, and the use of learning methods reached 69%. In the second cycle, the preparation of Lesson Plans reached 74%, the implementation of teaching and learning activities reached 77%, and the use of learning methods reached 82%. Based on the results of the school action research the ability of teachers in the use of learning methods through clinical supervision has increased.